PENGARUH PROFESIONALISME DAN KOMPETENSI TERHADAP KINERJA AUDITOR BADAN PENGAWAS KEUANGAN - Johannes .; Edward .; Suhaibah Kadarsih (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2014)
High expectation on BPKperformance makes BPK continously make effort to improve the quality of auditor by increasing auditors’s professionalisme and competencies. The purpose of this research is to explain the effect of professionalism and competency on auditor’s performance. Samples is as many as 49 auditors that chosen from the population inBPK. Research result showed that the professionalism and competency has a positive effect on auditor’s performance. Based on the research result it is recommended that all the auditors shoul be encouraged to self competencies and professionalism to make BPK as an organization to be more perform to establish good governance. Keywords: professionalism, competency, performance, BPK